1995
DOI: 10.1021/j100045a022
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Exchange and Jahn-Teller Inversion on Cu2+ in Water and N,N'-Dimethylformamide: A High-Pressure 17O NMR Study

Abstract: We have measured the longitudinal and transverse l70 NMR relaxation rates and chemical shifts in solutions of Cu2+ in DMF as a function of temperature, pressure, and magnetic field. The temperature and magnetic field dependence of the transverse relaxation rates and chemical shifts yields the following kinetic parameters for DMF exchange on [Cu(DMF)(,]2+: k«298 = (9.1 ± 2.4) x 108 s-1 [lifetime rm298 = (1.1 ± 0.4) x 10-9 s] with activation parameters AH* = 24.3 ± 1.2 kJ mol-1 and AS* = 8.1 ± 4.6 J K.-1 mol-1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 3 publications
5
36
0
Order By: Relevance
“…At the same time the substitution reactions of poorly nucleophilic ligands including solvent molecules on copper(II) complexes were found to proceed by a dissociative interchange (I d ) mechanism [39,40,[52][53][54][55][56]. This is evidenced, in particular, by positive values of the activation volume (DV 6 ¼ ) for solvent exchange reactions of methanol (+8.3 cm 3 mol À1 ) [53], water (+2.0 cm 3 mol À1 ) [54], and DMF (+8.4 cm 3 mol À1 ) [54] on hexasolvento Cu 2+ .…”
Section: Ligand Exchangementioning
confidence: 99%
“…At the same time the substitution reactions of poorly nucleophilic ligands including solvent molecules on copper(II) complexes were found to proceed by a dissociative interchange (I d ) mechanism [39,40,[52][53][54][55][56]. This is evidenced, in particular, by positive values of the activation volume (DV 6 ¼ ) for solvent exchange reactions of methanol (+8.3 cm 3 mol À1 ) [53], water (+2.0 cm 3 mol À1 ) [54], and DMF (+8.4 cm 3 mol À1 ) [54] on hexasolvento Cu 2+ .…”
Section: Ligand Exchangementioning
confidence: 99%
“…37 In Fig. 5 is visualized the trend in variation of the rate constant, kf, of the TPP-SAT complex formation in AN for a series of M 2+ ions and in the rate constant, kex, of the solvent exchange in H2O, [81][82][83][84][85] methanol, [86][87][88] DMF, [88][89][90][91] and AN. 88,[92][93][94][95] Although the values of kex for the solvent exchange on the Cu 2+ and Zn 2+ ions in AN are not available, the variation in kex for a series of M 2+ ions is similar for various solvents, as expected from Fig.…”
Section: ·3 Mechanism Of Sat Complex Formationmentioning
confidence: 99%
“…It was determined to be þ 2.1 cm 3 /mol in a later report signifying the likelihood of an I d mechanism. 188 It was also shown that DMF was exchanged on [Cu(DMF) 6 ] 2 þ by an I d mechanism (DV " ¼ þ 8.4 cm 3 /mol), a reflection of the greater bulk of the DMF ligand. Indeed, DMF exchange on [Mn(DMF) 6 ] 2 þ is characterized by a positive value of DV " , whereas the hexaaqua Mn(II) ion has a small negative DV " and proceeds to exchange water with an I a mechanism (see above).…”
Section: Transition Metal Ions (D)mentioning
confidence: 99%
“…Indeed, DMF exchange on [Mn(DMF) 6 ] 2 þ is characterized by a positive value of DV " , whereas the hexaaqua Mn(II) ion has a small negative DV " and proceeds to exchange water with an I a mechanism (see above). 188 The mechanism of solvent exchange has not been in dispute, but relatively recently based on neutron diffraction experiments and supported by molecular dynamics simulations, it was proposed that the Cu(II) aqua ion exhibits five-fold coordination. 189 It was argued that the earlier experimental data could be rationalized on the basis of a five-coordinate metal center, and the k EX value for water was modified to k EX ¼ 5.7 Â 10 9 s À1 .…”
Section: Transition Metal Ions (D)mentioning
confidence: 99%